Rasch Model Scale Fit Applied to the Parental Stress Index-Short Form (PSI/SF) - Burga, Andrés (2016)
The purpose of this study is to determine whether the Parental Stress Index-Short Form (PSI/SF) fits the unidimensional Rasch model. An intentional non-probabilistic sample composed of 370 parents from metropolitan Lima with children aged 0 to 3 was used. Results indicate that the 23 items in this proposed version show a good fit to the Rasch model. There are good reliability scores derived from the application of this instrument.